Realizing the potential of mobile interventions for education - Jasmin Breitwieser; Andreas B. Neubauer; Florian Schmiedek; Garvin Brod (npj Science of Learning)
Abstract Mobile devices are ubiquitous, but their potential for adaptive educational interventions remains largely untapped. We identify three key promises of mobile interventions for educational research and practice: 1) intervening when it is most beneficial (i.e., “just-in-time adaptivity”), 2) estimating causal effects of interventions in ecologically valid settings, 3) considering the impact of context on the effectiveness of interventions. We discuss the challenges and next steps to advance this field.